Construction of a multiple-regression model for estimating the force in tethered swimming, and power in semi-tethered swimming for males - Kimura, T.; Ohba, M.; Shionoya, A. (Procedia Engineering, 2013)
The purposes of this study were to clarify the relationship between the force in tethered swimming (TS) and the power in semi-tethered swimming (STS), and to develop multiple regression models to estimate the force in the TS and the power in the STS using plural physical elements. To perform these purposes, the force in the TS and the power in the STS of 53 elite male high school and junior high school swimmers as subjects were measured. The force in the TS was measured by an electrical digital force gauge. The power in the STS was measured by the ergometer attachment improved a bicycle ergometer. Furthermore, height(163.2 cm in average), weight (51.6 kg), finger reach span (168.4 cm), foot length (26.1 cm), vertical jump (43.0 cm) and its power of each subject was measured. The results of this study were summarized as follows; 1) The relationships between the force in the TS (X) and the power in the STS (Y) was Y=0.182X+16.35 (r=0.814). This relationship was highly significant statistically (p<0.001). 2) 49 of the multiple regression models to estimate the force in the TS were derived. The highest correlation coefficient model in theses was as follows; TS=0.16×weight+0.75×age+0.03×finger reach span+1.10×foot length+0.22×vertical jump-41.68 (r=0.787). 3) 59 of the multiple regression models to estimate the power in the STS were derived. The highest correlation coefficient model in these was as follows; STS=0.03×height+0.45×weight+2.26×age+0.41×finger reach span+0.27×vertical jump+0.01×vertical jump power-88.56 (r=0.866).